Knowledge and attitude regarding dengue fever among undergraduate students in UiTM Puncak Alam / Noor Zafirah Awang , Nurul Farahana Abdul Kudus and Siti Noorhanny Nor Azmi - Awang, Noor Zafirah; Abdul Kudus, Nurul Farahana; Nor Azmi, Siti Noorhanny (Faculty of Health Sciences, 2015)
Background: Dengue is among the most well-known mosquito-borne viral illnesses attacking people. Prevalence of Dengue fever among Malaysians has been worsened each year with an increasing numbers of reported cases and its more severe forms clearly calls attention to the importance of knowledge and attitudes toward the prevention of dengue. Objective: The study aims to assess the knowledge and attitudes regarding Dengue Fever among university students in UiTM Puncak Alam campus. Methodology: A cross-sectional study using self-reported questionnaires was conducted among 366 undergraduate students of UiTM Puncak Alam. The data were analysed using SPSS version 20.0. Results: Only 57 (15.6%) of undergraduate students have good knowledge on Dengue Fever while 290 (79.2%) students have good attitudes towards Dengue Fever. There were no statistically significant associations between most sociodemographic factors (with score of knowledge regarding Dengue Fever except for faculty; p=0.01. There were also no statistically significant associations between most socio-demographic factors with attitude regarding Dengue Fever. Conclusion: Undergraduate students have excellent attitude regarding Dengue Fever. However, the level of knowledge was poor where less than quarter of the participants able to achieve the good level of knowledge on Dengue Fever.